Maternal phthalate exposure during pregnancy and male reproductive disorders: a systematic review and metaanalysis - Yu, Chengjun; Lu, Jiandong; Zhao, Jie; Zhao, Tianxin; Long, Chunlan; Lin, Tao; Wu, Shengde; Wen, Sheng; Wei, Guanghui (The Turkish Journal of Pediatrics, 2022)
Background. Phthalates are ubiquitous in the environment and they can penetrate the human body via multiple routes. However, the impact of phthalates on human male reproductive disorders remains unclear. Methods. A critical review of published studies was conducted to clarify the association of phthalates and male reproductive disorders and to highlight future research needs. PubMed, Cochrane Library, and Web of Science Database were systematically searched for relevant articles written in English, independent of region and time period. If more than one paper overlapped in study design or participants included, the most recent manuscript was included in our review. Due to limited homogeneous statistical data, observed trends were summarized to draw approximate conclusions. Results. Nineteen manuscripts were included in our final analysis. Exposure to di-(2-ethylhexyl) phthalate (DEHP), di-n-butyl phthalate (DBP), diethyl phthalate (DEP), and/or benzyl butyl phthalate (BBP) is associated with a shorter anogenital distance (AGD). Meanwhile, exposure to DEHP and/or di-isodecyl phthalate (DIDP) is associated with higher risks for cryptorchidism and hypospadias. Conclusions. Generic exposure to phthalates has an adverse effect on human reproductive development, especially exposure to DEHP, DBP, DEP, BBP, and DIDP. A critical time for exposure sensitivity is during early pregnancy. Due to the lack of significant statistical power in this study, the conclusions drawn should be cautiously interpreted and they remain to be validated. Thus, additional well-designed studies, as well as propaganda and education regarding phthalate exposure and safer substitutes for these compounds, are greatly needed.